Cloud-Powered Neural Networks: The Democratization of Deep Learning through Cloud Computing - Venugopal, Vimal Pradeep (International Journal of Computing and Engineering, 2025)
The democratization of deep learning through cloud computing represents a transformative shift in artificial intelligence accessibility, breaking down traditional barriers that once limited participation to well-funded institutions. This article explores how cloud platforms have revolutionized access to specialized computing infrastructure, reduced financial obstacles through flexible pricing models, and introduced technical enablers that simplify AI implementation. The emergence of collaborative ecosystems and knowledge sharing mechanisms has fostered global research communities that transcend geographical and institutional boundaries. These developments have catalyzed real-world applications across consumer technologies, business operations, and scientific research, particularly in healthcare. Looking ahead, the continuing co-evolution of cloud services and AI capabilities promises further advancements in accessibility while presenting new challenges related to skills gaps, economic disparities, and regulatory frameworks. This article examines both the technological innovations driving AI democratization and their broader societal implications.